1991
DOI: 10.1159/000200718
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Free Radicals and Lipid Peroxidation in the Pathogenesis of Gastric Mucosal Lesions Induced by Indomethacin in Rats

Abstract: The relationship of gastric hypermotility to mucosal hemodynamics, lipid peroxidation and vascular permeability changes was investigated in the pathogenesis of indomethacin-induced gastric lesions in rats. Subcutaneous administration of indomethacin (25 mg/kg) produced an increase in both the amplitude and frequency of stomach contraction from 30 min after treatment, resulting in hemorrhagic damage 2 h later. Gastric mucosal blood flow measured by a Laser flowmetry showed oscillatory fluctuations under hyperco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
165
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(176 citation statements)
references
References 22 publications
(34 reference statements)
11
165
0
Order By: Relevance
“…This idea was supported by the present findings that the microvascular permeability was markedly increased in adrenalectomized rats, irrespective of whether or not they were given indomethacin, and that this alteration was totally inhibited by supplementations of corticosterone. Previous studies (39) suggested that the increase of gastric microvascular permeability in indomethacin-treated rats is caused by vascular disturbances due to abnormal contraction of the stomach wall mediated by several events, including neutrophil-endothelial interaction. It is assumed that the effect of corticosterone on the microvascular permeability is brought about by its inhibitory action on gastric hypermotility induced by indomethacin through amelioration of glucose metabolism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This idea was supported by the present findings that the microvascular permeability was markedly increased in adrenalectomized rats, irrespective of whether or not they were given indomethacin, and that this alteration was totally inhibited by supplementations of corticosterone. Previous studies (39) suggested that the increase of gastric microvascular permeability in indomethacin-treated rats is caused by vascular disturbances due to abnormal contraction of the stomach wall mediated by several events, including neutrophil-endothelial interaction. It is assumed that the effect of corticosterone on the microvascular permeability is brought about by its inhibitory action on gastric hypermotility induced by indomethacin through amelioration of glucose metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, indomethacin shows potent ulcerogenic action in experimental animals (38,44). The mechanism by which indomethacin induces gastric injury is generally considered to involve depletion of PGs, yet it has proven more complicated than expected and involves multiple, closely interacting elements such as gastric hypermotility, microcirculatory disturbances, neutrophil-endothelial cell interactions, and superoxide radicals, in addition to PG deficiency (39,44).…”
mentioning
confidence: 99%
“…The neutrophil infiltration in gastric mucosa induced by ethanol has been shown to be closely related to the formation of lesions [10]. Determination of myeloperoxidase (MPO) activities, which are deemed as the main marker of neutrophil infiltration, is one of the main indicators of gastric injuries [11]. The invasion of stomach tissues marked by neutrophils with increased MPO activity causes gastric mucosa injury [12].…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms like decreased gastric mucosal blood flow (K ita g a w a et al. 1979), increased gastric motility ( Gar ric k et al 1986), acetylcholine as a mediator of vagal hyperactivity (G a ton et al 1993), decreased prostaglandin serum (M i II e r 1987) or mucosa level (G it lin et al 1988), and increased vascular permeability (Takeuchi et al 1991) are supposed to be involved in ulcer development. Recently, attention has been focused on the role of reactive oxygen species (ROS).…”
mentioning
confidence: 99%
“…ROS have been found to play a role in experimental gastric damage induced by immobilization (M a n c in ell i et al. 1990), hemorrhagic shock ( Ito hand Gut h, 1985), reperfusion (P err y et al 1986), and nonsteroidal antiinflammatory drugs ~Takeuchi et al 1991). It is assumed that the gastric damage in rats induced by Immobilization stress may have a pathogenic mechanism in common with other types ?f stress.…”
mentioning
confidence: 99%